Evaluation of four ionic liquids for pretreatment of lignocellulosic biomass - Gräsvik, John (BioMed Central, 2014)
BACKGROUND: Lignocellulosic biomass is highly recalcitrant and various pretreatment techniques are needed to facilitate its effective enzymatic hydrolysis to produce sugars for further conversion to bio-based chemicals. Ionic liquids (ILs) are of interest in pretreatment because of their potential to dissolve lignocellulosic materials including crystalline cellulose. RESULTS: Four imidazolium-based ionic liquids (ILs) ([C=C(2)C(1)im][MeCO(2)], [C(4)C(1)im][MeCO(2)], [C(4)C(1)im][Cl], and [C(4)C(1)im][HSO(4)]) well known for their capability to dissolve lignocellulosic species were synthesized and then used for pretreatment of substrates prior to enzymatic hydrolysis. In order to achieve a broad evaluation, seven cellulosic, hemicellulosic and lignocellulosic substrates, crystalline as well as amorphous, were selected. The lignocellulosic substrates included hybrid aspen and Norway spruce. The monosaccharides in the enzymatic hydrolysate were determined using high-performance anion-exchange chromatography. The best results, as judged by the saccharification efficiency, were achieved with [C(4)C(1)im][Cl] for cellulosic substrates and with the acetate-based ILs for hybrid aspen and Norway spruce. After pretreatment with acetate-based ILs, the conversion to glucose of glucan in recalcitrant softwood lignocellulose reached similar levels as obtained with pure crystalline and amorphous cellulosic substrates. IL pretreatment of lignocellulose resulted in sugar yields comparable with that obtained with acidic pretreatment. Heterogeneous dissolution with [C(4)C(1)im][HSO(4)] gave promising results with aspen, the less recalcitrant of the two types of lignocellulose included in the investigation. CONCLUSIONS: The ability of ILs to dissolve lignocellulosic biomass under gentle conditions and with little or no by-product formation contributes to making them highly interesting alternatives for pretreatment in processes where high product yields are of critical importance.